Effects of electromagnetic fields on the motion of Euglena gracilis. - Ascoli, C (1978)
The orientation behavior of Euglena gracilis cultures in electromagnetic fields is shown to agree with the predictions of a model involving only a passive mechanism. The increase in Euglena motor activity with increasing field intensity is demonstrated by measuring various motion parameters by the laser scattering technique. The effect of electric field on the speed of Euglenas is compared with that of temperature. We conclude that the electric field warms up the culture, thus inducing an increase in cell motility.